Pengembangan Instrumen Evaluasi Pembelajaran Ranah Psikomotorik pada Materi Shalat di MTs Darunna'im - Maulana, Hasan; Anshori, Irfan (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
Education is carried out to explore and then develop various competencies that already exist in each student. These competencies include abilities in the scientific field, attitudes, and skills. These three competency domains should be developed optimally and in a balanced way both in the learning process in class and in the implementation of assessments/evaluations. Facts on the ground show that the procedure for developing psychomotor evaluation of the prayer material at MTs Darunna'im using the R&D model has been able to produce a valid, reliable, objective, systematic, practical and effective assessment instrument. This study aims to develop a valid, reliable, objective, systematic, practical and effective psychomotor evaluation tool. The research activity consisted of two stages, namely development and limited trials. The development stage includes data analysis carried out in two stages, namely at the development stage and at the end of the limited trial. Analysis at the model development stage was carried out using qualitative and quantitative approaches. This means that the performance evaluation instrument is feasible to use.